MANAGEMENT OF ROOT- KNOT NEMATODE (MELOIDOGYNE INCOGNITA) INFECTING MULBERRY - NARASIMHAMURTHY, T.N.; REDDY, B.M.R.; PRAHALADA, G.D.; PRASAD, G.R. GURU; SHASHIKUMAR, H.N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
viride, 2x10“cfu/g) and commercial bioagents (Trichoderma viride, 2x10"cfu/g) and Psuedomonas fluorescens, 1x10fcfu/g) under field conditions. All the bioagents tested were effective in suppressing nematode population and improving plant growth and yield. However, higher shoot length (125.10cm), number of leaves (156.00) and leaf yield (3.57kg) were recorded in indigenous Tviride (a) 30g/m followed by indigenous T viride @ 20g/m, Pseudomonas fluorescens (commercial) and T viride (commercial) (d) 20g m. respectively. Lowest nematode population in soil (162.00) and root (25.33) were recorded in indigenous T. viride (a 30g/m treated plot followed by indigenous T viride @ 20g/m. Maximum reduction of galls (49.33) and egg masses (7.50) per five gram of root was recorded in indigenous T viride (a 30gsm compared to other treatments.